Geographical and altitudinal population genetic structure of two dung fly species with contrasting mobility and temperature preference - Kraushaar, U; Goudet, J; Blanckenhorn, W U (Heredity, 2002)
Local adaptation of populations requires some degree of spatio-temporal isolation. Previous studies of the two dung fly species Scathophaga stercoraria and Sepsis cynipsea have revealed low levels of geographic and altitudinal genetic differentiation in quantitative life history and morphological traits, but instead high degrees of phenotypic plasticity. These patterns suggest that gene flow is extensive despite considerable geographic barriers and large spatio-temporal variation in selection on body size and related traits. In this study we addressed this hypothesis by investigating genetic differentiation of dung fly populations throughout Switzerland based on the same 10 electrophoretic loci in each species. Overall, we found no significant geographic differentiation of populations for either species. This is inconsistent with the higher rates of gene flow expected due to better flying capacity of the larger S. stercoraria . However, heterozygote deficiencies within populations indicated structuring on a finer scale, seen for several loci in S. cynipsea , and for the locus PGM (Phosphoglucomutase) in S. stercoraria . Additionally, S. cynipsea showed a tendency towards a greater gene diversity at higher altitudes, mediated primarily by the locus MDH (malate dehydrogenase), at which a second allele was only present in populations above 1000 m. This may be caused by increased environmental stress at higher altitudes in this warm-adapted species. MDH might thus be a candidate locus subject to thermal selection in this species, but this remains to be corroborated by direct evidence. In S. stercoraria , no altitudinal variation was found.